PENGARUH MODEL PROJECT-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS DAN MOTIVASI BELAJAR SISWA PADA MATERI SEGIBANYAK - Aghnia, Farisa Rizqi Nurazka; Maulana, Maulana; Sudin, Ali (Jurnal Pena Ilmiah, 2019)
The role of mathematics in education is very important to develop the ability of students, whether in mathematics or other sciences. Through the project-based learning model, the teacher sees to optimize students' comprehension skills in understanding material concepts with a student center system to increase student learning passion. This study user the quasi-experimental design and research design method of the nonequivalent control group design. The population of the study was fourth-grade students in North Sumedang Subdistrict, with a sample of study namely Class IV students at SDN Sindang IV (control) and Class IV at SDN Sindang II (experiment). The conclusions obtained from the research, namely 1) The project-based learning model and conventional approaches can improve students' mathematical understanding and motivation abilities, 2) The project-based learning model is significantly better in improving mathematical understanding and motivation compared to the conventional approach.